What effect will pharmacogenomics have on mental health nursing?. (June 2013) - Currid, Thomas J; Mutsatsa, Stanley
SUMMARY Pharmacogenomics offers much hope and optimism for those who are ill. As the largest workforce in mental health, mental health nurses are pivotal in continuously striving for quality improvements for the mentally ill. In this paper, we offer a speculative perspective on the impact that pharmacogenomics will have on mental health nursing. Despite the associations that may be construed between pharmacogenomics and the medical model of practice, we argue that the use of medication is central to many patients' wellbeing and, therefore, pharmacogenomics offers many benefits to both patients and mental health nurses. Benefits include a more robust and accurate practice of prescribing, an enhanced role for the nurse and greater professional autonomy. We conclude by encouraging mental health nurses to take a proactive role in future pharmacogenomic developments.